2009
DOI: 10.1073/pnas.0902688106
|View full text |Cite
|
Sign up to set email alerts
|

Design of anti- and pro-aggregation variants to assess the effects of methionine oxidation in human prion protein

Abstract: Prion disease is characterized by the ␣3␤ structural conversion of the cellular prion protein (PrP C ) into the misfolded and aggregated ''scrapie'' (PrP Sc ) isoform. It has been speculated that methionine (Met) oxidation in PrP C may have a special role in this process, but has not been detailed and assigned individually to the 9 Met residues of full-length, recombinant human PrP C [rhPrP C (23-231)]. To better understand this oxidative event in PrP aggregation, the extent of periodate-induced Met oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 57 publications
6
104
0
4
Order By: Relevance
“…It was suggested that methionine oxidation could trigger misfolding. This hypothesis was later corroborated by experimental studies of recPrP that used norleucine and methoxinine as analogues of the hydrophobic, non-oxidized form or the hydrophilic oxidized form of methionine, respectively [165]. The norleucine variant exhibited a stabilized α-helical structure and low aggregation propensity, whereas the methoxinine variant largely consisted of β-structure and had a high tendency to aggregate.…”
Section: In Vivo Modificationsmentioning
confidence: 85%
“…It was suggested that methionine oxidation could trigger misfolding. This hypothesis was later corroborated by experimental studies of recPrP that used norleucine and methoxinine as analogues of the hydrophobic, non-oxidized form or the hydrophilic oxidized form of methionine, respectively [165]. The norleucine variant exhibited a stabilized α-helical structure and low aggregation propensity, whereas the methoxinine variant largely consisted of β-structure and had a high tendency to aggregate.…”
Section: In Vivo Modificationsmentioning
confidence: 85%
“…Indeed, for example, oxidation of a Met residue has been reported in an A␤ peptide forming senile plaques of Alzheimer's diseases (31) and also in infectious forms of PrP proteins in prion diseases (32). Furthermore, the effects of Met oxidation on the kinetics of fibrillar aggregation in vitro have been examined in several disease-related proteins such as ␣-synuclein (33), PrP (34), and ApoA-I (35). In these previous studies, oxidative modifications have been assumed to precede the aggregation of protein molecules and thereby affect its formation kinetics; however, it remains obscure when proteins are oxidized during the formation of pathological inclusions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also precedent for Met oxidation causing large-scale changes in protein structure (Griffiths and Cooney 2002;Wolschner et al 2009;Pan et al 2010;Marondedze et al 2013). If this were the case, it might easily lead to exposure of a previously cryptic phosphorylation site or to hide a previously exposed site.…”
Section: Crosstalk Between Met Oxidation and O-phosphorylationmentioning
confidence: 99%